Natural flavones from edible and medicinal plants exhibit enormous potential to treat ulcerative colitis - Lu, Qiang; Xie, Yuhong; Luo, Jingbin; Gong, Qihai; Li, Cailan (Frontiers in Pharmacology, 2023)
Ulcerative colitis (UC) is a chronic aspecific gut inflammatory disorder that mainly involves the recta and colons, and mostly presents as a long course of repeated attacks. This disease, characterized by intermittent diarrhoea, fecal blood, stomachache, and tenesmus, severely decreases the living quality of sick persons. UC is difficult to heal, has a high recurrence rate, and is tightly related to the incidence of colon cancer. Although there are a number of drugs available for the suppression of colitis, the conventional therapy possesses certain limitations and severe adverse reactions. Thus, it is extremely required for safe and effective drugs of colitis, and natural-derived flavones exhibited huge potential. The present study focused on the advancement of natural-derived flavones from edible and pharmaceutical plants for treating colitis. The underlying mechanisms of natural-derived flavones treating UC were tightly connected with the regulation of gut barrier function, immune-inflammatory reactions, oxidative stress, gut microflora, and SCFAs production. The prominent effects and safety of natural-derived flavones make them promising candidate drugs for colitis treatment.